Effect of summer cover crops on cabbage yield, weed suppression, and N mineralization in a low input cropping system - Bilenky, Moriah T.; Nair, Ajay; McDaniel, Marshall D. (Frontiers in Sustainable Food Systems, 2022)
Summer cover crops (SCC) provide valuable agroecosystem services to growers using spring and autumn vegetable crop rotations. Choosing the right SCCs to maximize agroecosystem services and fit growers’ interests is challenging due to the wide array of SCC functions and one benefit may come at the cost of another (i.e. a tradeoff). In particular, fast-growing grasses may produce greater SCC biomass but may immobilize plant-available N needed by the autumn vegetable crop. We conducted a field study in Ames, Iowa US to compare agroecosystem services –weed suppression, autumn cabbage yield, soil nutrients, and net nitrogen (N) mineralization of eight SCC species over two years. Cover crop species were grown for an average of 55 days and included: brown top millet (Panicum ramosum L., BTM), buckwheat (Fagopyrum esculentum Moench, ‘Mancan’, BW), cowpea (Vigna unguiculata (L). Walp., ‘Iron and Clay’, CP), flax (Linum usitassimum L. ‘Golden’, GF), mung bean (Vigna radiata (L.) R. Wilczek, MB), sunnhemp (Crotalaria juncea L., SH), sorghum sudangrass (Sorghum bicolor L. Moench x Sorghum sudanense Piper Staph. ‘Sorgrow BMR Dwarf’), SS), and Teff grass (Eragrostis tef (Zuccagni) ‘Selam’, TEF), and a no-SCC control (NCC) treatment. The range of mean cover crop biomass was 0.8 (cowpea) to 7.5 (teff grass) Mg ha-1. There was a strong, negative correlation between SCC biomass and weed biomass (R2 = 0.83). Low biomass producing legumes resulted in greater weed biomass, but 34 - 58% greater cabbage yield in one of two experimental years. Ion exchange membranes (IEMs) were not able to capture differences in total net N mineralization among SCC treatments however, soil inorganic N was greater under legume SCCs at SCC termination. We show there are tradeoffs when choosing SCCs between weed suppression and net N mineralization and that the environmental conditions, i.e., climate, regulate whether these tradeoffs favor greater vegetable crop yields.